2020
DOI: 10.5944/rppc.28107
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of the COVID-19 pandemic: Negative and positive effects in Spanish population during the mandatory national quarantine

Abstract: The COVID-19 pandemic has been spreading rapidly in Spain. The objective of this work was to examine the psychological impact of the pandemic and the Spanish national quarantine that took place during March and April 2020. We investigated the prevalence of fear of coronavirus, emotional symptoms and sleep problems. We also examined possible positive effects. A sample of 1,161 participants (aged 19 to 84 years) completed online the Coronavirus Psychological Impact Questionnaire, the Intolerance of Uncertainty S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
75
1
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 14 publications
12
75
1
13
Order By: Relevance
“…Spanish citizens were not allowed to leave their homes unless they were considered essential workers, went out for food shopping or for health issues ( Boletín Oficial del Estado, 2020a , b ). Similarly to what has been reported in other places ( Brailovskaia et al, 2020 ; Cénat et al, 2020 ), the negative psychological impact of the lockdown in Spain has already been highlighted ( Giménez-Dasí et al, 2020 ; González-Sanguino et al, 2020 ; Justo-Alonso et al, 2020 ; Sandín et al, 2020 ). Among other emotional symptoms, high levels of depression, anxiety, stress, worries, feelings of loneliness and sleep problems have been reported in adults of various ages ( Justo-Alonso et al, 2020 ; Sandín et al, 2020 ).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Spanish citizens were not allowed to leave their homes unless they were considered essential workers, went out for food shopping or for health issues ( Boletín Oficial del Estado, 2020a , b ). Similarly to what has been reported in other places ( Brailovskaia et al, 2020 ; Cénat et al, 2020 ), the negative psychological impact of the lockdown in Spain has already been highlighted ( Giménez-Dasí et al, 2020 ; González-Sanguino et al, 2020 ; Justo-Alonso et al, 2020 ; Sandín et al, 2020 ). Among other emotional symptoms, high levels of depression, anxiety, stress, worries, feelings of loneliness and sleep problems have been reported in adults of various ages ( Justo-Alonso et al, 2020 ; Sandín et al, 2020 ).…”
Section: Introductionsupporting
confidence: 70%
“…Individual differences related to personal and contextual variables have also been noted. Within the former, the negative emotional impact is higher in women than in men, and in younger than in older adults ( González-Sanguino et al, 2020 ; Justo-Alonso et al, 2020 ; Sandín et al, 2020 ). Resilience -the capacity of dealing with adversities as challenges- has been found to be a protective factor of the psychopathologies related to the pandemic ( Luceño-Moreno et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical levels of anxiety, depression, and stress found in around one-third of the participants are broadly in line with other similar studies [ 4 , 8 , 13 , 47 ]. The bulk of these studies were conducted in China but there are also similar results from studies in Bangladesh [ 5 ], India [ 7 ], Italy [ 9 ], Vietnam [ 10 ], United Kingdom [ 12 ], and Spain [ 11 , 17 ].…”
Section: Discussionmentioning
confidence: 74%
“…The effects of the pandemic on mental health, both of the frontline health workers actively engaged in the struggle against the disease and of the general population under lockdown, have also been a major area of research as some of the most significant side effects of COVID-19 [ 3 ]. Several studies [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ] have reported a considerable rise in adult mental disorders during the COVID-19 lockdown; children’s psychological well-being has also been found to be seriously affected [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mandatory at-home lockdown for the entire Spanish population led to significant habit changes that affect individual well-being [ 18 ]. Although some studies with Spanish samples have been published (i.e., [ 19 , 20 ]), studies are needed at the population level, that would be representative enough to delving deeper into the factors related to the psychological impact of COVID-19 and generalizing the findings to the population.…”
Section: Introductionmentioning
confidence: 99%